Characteristics of rail deformation caused by tunnel floor heave and corresponding running risk of high-speed train. (5th September 2022) - Liu, Y.; Song, H.L.; Sun, X.D.; Xing, H.P.; Feng, C.Y.; Liu, J.F.; Zhao, G.T.
Highlights: A four-year-long observation of uneven rail deformation is performed in two HSR tunnels. The predominant wavelength and amplitude of rail deformation in tunnel are 3–30 m and 2–10 mm, respectively. The heave transfer within track structure exhibits more significantly on wavelength than on amplitude. Speed raising has strong effects on the magnitude and location of wheel-rail contact force. The risk of derailment and passenger comfort is more sensitive to short- and long-wavelength floor heave, respectively. Abstract: Floor heave is a huge threat to the safe operation of high-speed trains in tunnels. However, rare research recognizes the characteristics of the rail irregularity caused by tunnel floor heave and the corresponding running risk of high-speed trains. In this paper, uneven rail profiles observed within four years in two HSR tunnels are used to investigate the temporal variation and spatial distribution of tunnel floor heave. The predominant wavelength and amplitude of the heave profile are determined. Hypothetic floor heave profiles with a wide range of wavelength and amplitude are used as the input in the simulation of the dynamic response of a VRT (vehicle-rail-track) system. Based on the simulation, the transfer laws for the wavelength and amplitude of heave within the track structure are revealed. The wheel-rail contact force, the wheel load reduction rate, and the sperling factor under various floor heave profiles are calculated. The floor heave profile that may lead to a high risk of derailment and low passenger comfort is presented for two train speeds. The research reveals that the predominant range of the wavelength for the rail heave in the tunnel is from 3 m to 30 m, and that of the amplitude is 2 mm to 10 mm. The heave transfer law within the track structure is strongly affected by both the wavelength and amplitude of the floor heave profile. The deformation of the rail varies more significantly on wavelength than on amplitude. Speed raising strongly influences the wheel-rail contact force, the wheel load reduction rate, and the sperling factor. The passenger comfort is more sensitive to longer-wavelength floor heave, whereas the risk of the derailment is more sensitive to shorter-wavelength floor heave.